Insights into the phase transformation of NiCo2S4@rGO for sodium-ion battery electrode. (1st April 2020) - Sun, Zhihui; Zhao, Chenglong; Cao, Xuecheng; Zeng, Kai; Ma, Zhaohui; Hu, Yongsheng; Tian, Jing-Hua; Yang, Ruizhi
Abstract: A promising hybrid anode material for sodium ion batteries (SIBs) is designed and synthesized by coating reduced graphene oxide onto NiCo2 S4 nanoparticles (denoted as NCS@rGO). An intrinsic 3D micro-mesoporous network is obtained, which can shorten and fasten the access of Na + diffusion and electron transport, provide sufficient reaction active sites, and enhance structural stability to suppress volume expansion. As a result, as an anode for SIBs, the NCS@rGO electrode delivers reversible capacity of 621 and 532 mAh g −1 at 0.1 and 0.5 A g −1, respectively. A high capacity retention of 95% is obtained at 0.1 A g −1 after 100 cycles. The reaction mechanism of NCS@rGO during charge and discharge has been investigated. The results reveal that the conversion products of NiS2 and CoS2 from the phase transformation of NiCo2 S4 are successfully confined with the rGO coating. Furthermore, the NCS@rGO hybrid exhibits a pseudo-capacitive dominated behaviour, which contributes to the measured superior rate capability. This work provides valuable insight into how the phase transformation of NCS@rGO during the charge/discharge process affecting the performance of sodium ion batteries, and this hybrid can be applied as a promising anode for SIBs. Graphical abstract: A promising hybrid NiCo2 S4 @rGO, using rGO as a protective matrix, is synthesized and exhibits excellent performance for the anode of SIBs. The reaction mechanisms during charge and discharge have been revealed. The decomposition products of NiS2 and CoS2 from the phase transformation of NiCo2 S4 are successfully confined by the rGO coating, which makes the hybrid a promising anode material for SIBs. Image 1 Highlights: NCS@rGO has been prepared by a hydrothermal method to form a mosaic structure. NCS@rGO shows excellent electrochemical performance as the anode material for SIBs. Insights into the phase transformation of NCS@rGO has been provided. Pseudo-capacitive dominated behaviour contributes to the superior rate capability.